Plasma alemtuzumab levels in patients with chronic lymphocytic leukemia treated with alemtuzumab combined with chemotherapy reflect the efficacy of the treatment: a hypothesis. Issue 4 (April 2013) - Vojdeman, Fie Juhl; Jurlander, Jesper; Veer, Mars van't; Itälä-Remes, Maija; Kimby, Eva; Tjønnfjord, Geir Erland; Walewski, Jan; Kozák, Tomas; Polliack, Aaron; Montagna, Michela; Regazzi, Mario; Kirkby, Nikolai; et al.
Abstract In the HOVON68 trial comparing subcutaneous low-dose alemtuzumab (LD-A) used together with fludarabine (F) and cyclophosphamide (C) with FC alone in high-risk chronic lymphocytic leukemia (CLL), LD-AFC resulted in significantly more clinical and molecular responses than FC, but also in more opportunistic infections. In a subgroup analysis of alemtuzumab trough levels during treatment by a sensitive enzyme-linked immunosorbent assay (ELISA) method, detectable levels were found in 4/6 complete and 0/3 partial responders. A relationship between alemtuzumab plasma levels, response and duration of lymphocytopenia was evident. We hypothesize that following combination therapy, the response may not be a function of the alemtuzumab levels, but the opposite, that plasma alemtuzumab levels are a function of the efficacy of the entire treatment, and the fewer leukemic target cells that are remaining, the higher are the levels of plasma alemtuzumab. This concept may well provide a guide for alemtuzumab dosage in future trials.